2017
DOI: 10.1080/09540121.2017.1332333
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of factors associated with social support satisfaction among HIV-positive young Black men who have sex with men

Abstract: This study examined the long-term predictors of social support satisfaction among HIV-positive young Black men who have sex with men (YBMSM). Data were collected across three waves between October 2012 and November 2014 as part of the baseline assessment from Project nGage, a preliminary efficacy randomized control study examining the role of social support in improving HIV care among YBMSM. The sample included 92 YBMSM aged 18-29. Major results controlling for age, education and intervention effects indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The fact that the variable "satisfaction with support", although being part of the same construct, is different from "number of supporters", was considered controversial, given that the number of supporters is described by classical researchers on this topic as an important predictor of satisfaction with support (14,25) . Some recent studies with other populations reinforce this evidence, pointing out that networks with more supporters increase the chances of the individual having more confident, interested, and less directive people (26)(27) to count on. Nonetheless, there are also results in recent literature that are similar to those of the present study, which have suggested that satisfaction with support assumes greater relevance as an analysis variable in studies on quality of life and health (8,28) .…”
Section: Discussionmentioning
confidence: 84%
“…The fact that the variable "satisfaction with support", although being part of the same construct, is different from "number of supporters", was considered controversial, given that the number of supporters is described by classical researchers on this topic as an important predictor of satisfaction with support (14,25) . Some recent studies with other populations reinforce this evidence, pointing out that networks with more supporters increase the chances of the individual having more confident, interested, and less directive people (26)(27) to count on. Nonetheless, there are also results in recent literature that are similar to those of the present study, which have suggested that satisfaction with support assumes greater relevance as an analysis variable in studies on quality of life and health (8,28) .…”
Section: Discussionmentioning
confidence: 84%
“…The pathway between perceived social support, depressive symptoms and disclosure to sexual partners may also vary by sex. Even though research examining social support among populations living with or at-risk for HIV tend to focus on either men [30,31] or women [32,33], and not both men and women, one study among European men and women living with HIV found that women reported a higher need for social support compared to men [28]. Risser et al, examined populations at-risk for HIV, and found that lack of social support from a significant other was associated with depressive symptoms for both men and women [34].…”
Section: Potential Moderation By Sexmentioning
confidence: 99%